Media Relations Strategy in Promoting Destination of Kutang Beach of Lamongan District, Indonesia - Rohimah, Afifatur; Ardilla, Yunita; Anam, Moh. Khoirul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Tourism becomes a wealth that will not run out otherwise tourism will continue to grow if the management is getting better. Media relations becomes one of the alternatives in helping the promotion process of a tourist destination. This study aims to analyze the media relations strategy in promoting tourist destinations that focus on the Kutang beach district Lamongan. This research applies a qualitative naturalistic method where there is no manipulation of an event (background) of research. The result of this research is the use of media relations to be one of the main components in improving the development of coastal tourism destinations. Use of media relations applied: 1) Press Release Activity, 2) Conference Press, 3) Event, 4) Press Message. Some of these activities carried out by involving the community, managers, government, and tourists, so that the implementation of media relations activities can be maximized. Some media relations activities that have been carried out are press release activities, press conferences, special events. One of which dominating is a special event because it is considered by the speaker as a simple activity that is able to have a tremendous impact, with the event, media partners from themselves will involve themselves in the event activities. Besides conducting media relations, it is also necessary to establish segmentation and clear segmenting. It is also necessary to do tourism differentiation to create sustainable tourism.